Refugee Law in India : The Road from Ambiguity to Protection - Sarker, Shuvro Prosun (Springer Singapore : Imprint: Palgrave Macmillan, 2017)
This book considers refugee protection mandates and addresses how legal scholarship can articulate a comprehensive and humane response to the contemporary refugee problem. Analyzing philosophical discourses and India's policies and practices on refugee protection, including judgments of Indian Courts in refugee related cases, it examines how organizational efforts can make these policies and practices equal for every refugee in India. It also surveys prevailing discriminative protection standards and entitlements developed through Conventions, Declaration and Directives, and compares and contrasts national refugee legislations in South Africa, Brazil and Canada. A key read for scholars and practitioners interested in the legal and policy implications of refugee protection, this text identifies various practices of nation-States from across the North/South divide and provides key insights into the evolving nature of protection agendas.
Keywords: Social sciences.; Emigration and immigration.; Welfare state.; Social justice.; Human rights.; elektronické knihy; electronic books